Severe Neuropsychiatric Reaction in a Deployed Military Member after Prophylactic Mefloquine - Peterson, Alan L.; Seegmiller, Robert A.; Schindler, Libby S. (Case Reports in Psychiatry, 2011)
Recent studies of military personnel who have deployed to Iraq and Afghanistan have reported a number of combat-related psychiatric disorders such as posttraumatic stress disorder, depression, and traumatic brain injury. This case report involves a 27-year-old male active-duty US military service member who developed severe depression, psychotic hallucinations, and neuropsychological sequelae following the prophylactic use of the antimalarial medication mefloquine hydrochloride. The patient had a recent history of depression and was taking antidepressant medications at the time of his deployment to the Middle East. Psychiatrists and other health care providers should be aware of the possible neuropsychiatric side effects of mefloquine in deployed military personnel and should consider the use of other medications for malaria prophylaxis in those individuals who may be at increased risk for side effects.